Supervising juveniles and adults: organizational context, professional orientations, and probation and parole officer behaviors - Bolin, Riane M. (Journal of crime and justice, 2018)
Observers of probation and parole suggest that organizational context and officers’ ‘working philosophy’ - how they see their job - may be instrumental in predicting supervision activities, yet few studies have examined this relationship. The present study contributes to the knowledge base on probation practices by examining the organizational context in which officers work - juvenile justice versus criminal justice - and officers’ individual work orientations on their tendencies to engage in various tasks related to supervising their clients. Data were collected through the use of an online questionnaire from a sample of juvenile and adult probation and parole officers employed in South Carolina during the spring of 2014. The study found that organizational context was a significant predictor of intended and actual behavior. On the other hand, professional orientation largely failed to significantly predict behavior. The implications of these findings are discussed.